(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
Satisfaction of employees depends on the incentive policy applied in the company. The incentive system should be adapted individually to the employees and the individual. The functioning of the system has a direct impact on the effectiveness of individual employees and on the operation of the entire unit.